(untitled) (Nexo Revista Científica, 2020)
In this study, we have sujessted a theoritical aproach via computing of nucleus-independent chemical shifts (S-NICS) in view point of probes motions in a sphere of de-shielding and shielding spaces of rings of anticancer contain heterocyclic rings. Few research in theoretical of a statistical approach in NMR shielding and nucleus independent chemical shifts for study of anticancer drugs. S-NICS method is an accurate method for estimation the amount of aromaticity in the non-benzene rings such as heterocyclic rings which is a famous for organic chemical compounds as anti-cancer disease. Theoretical of a statistical method of NICS-nucleus independent chemical shift in small distance and are alternate in large distance in the center of heterocyclic rings. In this research, we have explored the statistical approaches through nucleus-independent chemical shifts-SNICS calculations in view point of Bq motions in the center of sphere spaces of heterocyclic rings of some anticancer drugs. The S-NICS method is an accurate computing method for estimation the aromaticity in the non-benzene rings such as heterocyclic rings which are standard molecules in organic anti-cancer compounds. Although NICS values for benzene and naphthalene and so on can be indicated as aromaticity criterion, for other molecules such as heterocyclic rings and their derivatives, S-NICS values are much more accurate compare to NICS index. Hetrocyclic compound with good π stacks are good cacdidate for anticancer medicines. Precence of Nitrogen, oxygen and sulfur in these compounds make them similar biochemical parts such as nuclice acids and. Aromaticity of heterocyclic ring. This similarity especially them π stacks give the the ability of interaction with DNAs and RNAs and the heterocyclic compounds.